RETRACTED: Characteristics and Trends in Unethical Pro-organizational Behavior Research in Business and Management: A Bibliometric Analysis - Li, Zhihong (Frontiers in Psychology, 2022)
Unethical pro-organizational behavior is one of the core factors that affect organizational development. Although enterprises and researchers have done a lot of work, a quantitative and systematic assessment of unethical pro-organizational behavior research is still lacking, this review conducts a bibliometric analysis to describe the characteristics and trends of unethical pro-organizational behavior research in business and management, such as publication trend analysis, co-citation analysis, keywords co-occurrence analysis, and citation burst analysis. The results show that 89 articles and 4523 references from 49 journals contributed by 254 authors are identified. The number of publications has increased significantly since 2019. The China and United States are the most productive country. Umphress E and Yam C are the most influential authors. Journal of Business Ethics and Frontiers in Psychology are the most influential journal, 26 words in 516 keywords constitute the strongest set of terms available, Keyword co-occurrence analysis found ethical decision-making, the measurement and impact of unethical pro-organizational behavior, the antecedents of ethical leadership are worthy and prospective potential trends. These findings provide a systematically, transparently, and visually reviewed the landscape and development process of unethical pro-organizational behavior research, which may help researchers and practitioners to understand unethical pro-organizational behavior in business management and provide a new perspective for future research.